أثر الالتزام بمعايير التدقيق الجزائرية على جودة تقارير محافظ الحسابات - محمد نبيل, شايب (University of eloued جامعة الوادي, 2021)
لقد تناولنا في هذه الرسالة أثر الإلتزام بمعايير التدقيق الجزائرية على جودة تقارير محافظ الحسابات، وهدف هذه الدراسة معالجة إﺷﻜﺎل تم التطرق اليه من خلال مدخل حول التدقيق، محافظ الحسابات في الجزائر ومدى الإلتزام بمعايير التدقيق الجزائرية وجودة تقارير محافظ الحسابات والإطار التطبيقي للأثر المعايير على جودة التقارير للشركة محل الدراسة.In this thesis, we have discussed the impact of adherence to Algerian auditing standards on the quality of portfolio reports, and the aim of this study is to address a problem that was addressed in an introduction to auditing and portfolios in Algeria, compliance with Algerian auditing standards, the quality of portfolio reports, and the applied framework for the impact of standards on the quality of accounts reports for the company under study.
ماستر محاسبة وتدقيق
Keywords: التدقيق، معايير التدقيق الجزائرية، التقارير، محافظ الحسابات.; auditing, Algerian auditing standards, reports, portfolios of accounts.